RISM and inventorying early music manuscripts in Slovenia - Erjavec, Jana (Muzikološki zbornik, 2020)
Since its inception, the project Répertoire International des Sources Musicales (RISM) has played a major role in the creation of an inventory of preserved early music heritage in Slovenia. This article presents the background and the current state of cooperation between Slovenian musicology and the RISM project, focusing on the latest additions to the online catalogue from the music collection of the Church of St Daniel in Celje.
Keywords: Celje; cerkev sv. Danijela; Church of St Daniel; glasbeni katalogi; glasbeni rokopisi; music catalogues; music manuscripts; RISM; Slovene musicology; slovenska muzikologija